As disciplinas de exatas e o processo de ensino para alunos com deficiência visual na Universidade Federal de Sergipe - Santos, Flávio Correia (2014)
This work aims to analyze the methodologies and resources used by professors of exact sciences in their classes attended by visually impaired students at the Federal University of Sergipe. We opted to carry out qualitative research with a case study approach. The results indicate that it is not enough to implement an affirmative action policy with reserved seats at the university for disabled students. A large number of transformations should also take place in different aspects of the university, such as its physical structure, the faculty´s teaching practices, the curriculum, and also professors´ ongoing development in his/her work as a teacher of exact sciences. We come to the conclusion that the professors surveyed do not regard blind students as their students, but rather as a student of the university, which should be responsible for the learning process experienced by these students.